Cross With Caution: Antibiotic Cross-Reactivity and Co-Reactivity Patterns in Severe Cutaneous Adverse Reactions - Thompson, Grace; McLean-Tooke, Andrew; Lucas, Michaela (Frontiers in Immunology, 2021)
Current understanding of cross-reactivity in severe cutaneous adverse reactions to beta-lactam antibiotics is limited, thereby making recommendations for future prescribing difficult. The underlying immunopathogenesis of these reactions is not completely understood but involves interactions between small molecule drugs, T cells and HLA molecules. Historically, these reactions were considered to be specific to the inciting antibiotic and therefore likely to have minimal cross-reactivity. We assessed patients presenting with non-SJS/TEN severe cutaneous adverse reactions to a tertiary hospital drug allergy clinic. In our case series cross-reactivity or co-reactivity commonly occurred amongst the beta-lactam antibiotic class however further research is required to investigate and understand patterns of cross-reactivity. Based on our experience we provide clinicians with a practical algorithm for testing for cross-reactivity in non-SJS/TEN severe cutaneous adverse reactions.